1994
DOI: 10.1128/iai.62.7.2843-2848.1994
|View full text |Cite
|
Sign up to set email alerts
|

Fimbria-mediated adherence of Candida albicans to glycosphingolipid receptors on human buccal epithelial cells

Abstract: Candida albicans is an opportunist fungal pathogen that has the ability to adhere to host cell surface receptors via a number of adhesins. Yu et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 64 publications
1
34
0
1
Order By: Relevance
“…Unattached cells were removed from the strips by washing with 5 ml phosphate-buffered saline (PBS) solution. Subsequently, the strips were submerged in 4 ml of yeast nitrogen base (YNB) containing 50 mmol l )1 glucose and incubated over a series of time intervals (2,4,6,8,24 and 48 h) at 37°C. As negative controls, six strips were handled in an identical fashion, except that no Candida suspensions were added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unattached cells were removed from the strips by washing with 5 ml phosphate-buffered saline (PBS) solution. Subsequently, the strips were submerged in 4 ml of yeast nitrogen base (YNB) containing 50 mmol l )1 glucose and incubated over a series of time intervals (2,4,6,8,24 and 48 h) at 37°C. As negative controls, six strips were handled in an identical fashion, except that no Candida suspensions were added.…”
Section: Methodsmentioning
confidence: 99%
“…5 In fact, C. albicans has been demonstrated to bind to several cell types such as buccal epithelial cells, vascular endothelial cells, human corneocytes and vaginal epithelial cells. 6 Biofilms represent the most prevalent type of microbial growth in nature with significant implications in pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Candida can recognize stratherin, hydroxyapatite, and RGDcontaining proteins such as fibronectin and fibrinogen (213). Candida species also possess lectin-like adhesins, with binding to LacCer, asialo-GM1, Le a , and H-active glycans (213)(214)(215)(216)(217)(218)(219). The type of adhesin expressed varies by strain and is influenced by growth conditions (218)(219)(220).…”
Section: Candidamentioning
confidence: 99%
“…The receptor-binding domain (termed 'adhesintope') of the P. aeruginosa PAK pilin adhesin has been shown to reside in the carboxyterminal disulphide-looped region (PAK128-144) of the PAK pilin (Irvin et al, 1989;Lee et al, 1994;. C. albicans and other fungi have also been previously shown to bind to glycosphingolipids in vitro (Jimenez-Lucho et al, 1990) and we have established that C. albicans utilizes fimbriae to bind to asialo-GM 1 -like receptors on the surface of humans BECs (Yu et al, 1994b). We have also demonstrated that P. aeruginosa pili and synthetic C-terminal pilin peptides containing the pilus adhesin bind to asialo-GM 1 Sheth et al, 1994).…”
Section: Introductionmentioning
confidence: 80%
“…It has been demonstrated that one of the mechanisms by which C. albicans adheres to hBECs is mediated by the interaction of C. albicans fimbrial adhesins and glycosphingolipid (asialo-GM 1 ) on the surface of hBECs in vitro and that the ligand-binding domain on the asialo-GM 1 -like receptors is presumably located in a disaccharide (bGalNAc(1-4)bGal), i.e. the carbohydrate portion of asialo-GM 1 , since both asialo-GM 1 and synthetic b GalNAc(1-4)bGal can inhibit the binding of C. albicans fimbrial binding to asialo-GM 1 and hBECs (Yu et al, 1994b). As a putative receptor, asialo-GM 1 and its minimal disaccharide sequence (bGalNAc(1-4)bGal) can also significantly block C. albicans whole-cells binding to hBECs (Fig.…”
Section: Discussionmentioning
confidence: 99%